Novel electromagnetic acoustic transducer for measuring the thickness of small specimen areas - Sun, Hongjun; Urayama, Ryoichi; Hashimoto, Mitsuo; Kojima, Fumio; Uchimoto, Tetsuya; Takagi, Toshiyuki (International Journal of Applied Electromagnetics and Mechanics, 2019)
Intense ultrasonic waves are required to accurately measure the thickness of corroded specimen at a given point. The most intense part of the ultrasonic wave should be at the measurement point itself. In this paper, finite element simulation is used to optimize the structure of the classic racetrack coil bulk wave electromagnetic acoustic transducer to produce more intense, concentrated ultrasonic waves in a smaller area. In addition, a new magnet configuration is used that increases the wave intensity. Compared with the classic magnet configuration, the maximum amplitude of the ultrasonic wave is increased by 21%.